Robert Rauschenberg : breaking boundaries. - Mattison, Robert S. (London New Haven : Yale University Press London Yale University Press New Haven, 2003)
Lavishly illustrated with Rauschenberg's works and photographs of the artist in performance and in the studio, the mixture of the visual arts, politics, technology, dance, and urban theory - among other issues - covered in this study recommends it to a wide audience and speaks to the multidisciplinary scholarship of our era.
Robert Rauschenberg is one of the most prolific and best-known artists of the post-war period, whose work, ranging across a number of disciplines, has influenced avant-garde since the 1950s. Rauschenberg has allowed Robert Mattison into his studio to observe the artist at work and this resulting book examines selected projects in depth so that the meaning of his art, his working procedures, and the reasons behind his various artistic choices may be better understood.
The book covers the influence of urbanism on Rauschenberg's Combine paintings of the 1950s and explores his involvement with the "space race" during the 1960s and 1970s, relating his works to popular culture and demonstrating the development of his ideas about the peaceful exploration of space. Mattison examines Rauschenberg's extensive involvement in the performing arts, tracing his connections to avant-garde dance in America, addressing his own performances, and focusing on his work with the well-known choreographer Trisha Brown. The final chapter examines Rauschenberg's most extensive artistic undertaking, the Rauschenberg Overseas Culture Interchange (ROCI). One venue of this seven-year and eleven-country project was Chile, which Rauschenberg visited while the country was under the rule of dictator Augusto Pinochet. The author shows how in dangerous political circumstances Rauschenberg was able to execute and exhibit works critical of the government.
Engels
boek
Keywords: Rauschenberg, Robert